V zashchitu filosofii protiv pozitivizma i pragmatizma - Moris Kornfort ; obshchaia red. i vstup. stat'ia G. F. Aleksandrova. (Izdatel'stvo inostrannoi literatury, 1951)
Translation of "In defence of philosophy against positionism and pragmatism".Includes bibliographical footnotes.